Pesan Ritual dalam Pemindahan Ibu Kota Negara (Analisis Semiotika Roland Barthes pada Tayangan Live Youtube Sekretariat Presiden) - Ayu Yustian; Rifma Ghulam Dzaljad; Arya Athallah; Ghina Sabilla Lesmana (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The transfer of the National Capital City (IKN) in the IKN Zero Point Area, in Penajam Paser Utara Regency, East Kalimantan carries the concept of a modern city, a sustainable city and an international class city. President Joko Widodo inaugurated Law Number 3 of 2022 concerning the National Capital as proof of the government's seriousness towards the new National Capital. As a marker of the beginning of the construction of the IKN in East Kalimantan, on March 14, 2022, President Joko Widodo performed a Kendi Nusantara ritual. This ritual unites the land and water of 34 provinces in Indonesia into an Nusantara Jug. This ritual is thought to bring to life a long-abandoned mystical tradition. For this reason, researchers are interested in revealing the meaning of connotations, denotations, and myths in the Kendi Nusantara ritual based on the Youtube live streaming of the Presidential Secretariat. The results showed that from the 5 scenes analyzed, there was a meaning of denotation, namely describing the form of local wisdom of the unification of land and water. The meaning of connotation is a ritual that contains the hope that the development of IKN runs smoothly. The meaning of the myth signifies the support of the Indonesian people in the development of IKN in order to avoid danger and be protected by God Almighty. An important message in the Kendi Nusantara ritual describes the unity, unity and diversity of Indonesian society, although it is inversely proportional to the concept of IKN as a sophisticated and modern city but still practices irrational mystical rituals.